COVID-19 lockdown impact on physical activity and anxiety levels among physiotherapy practitioners, teaching faculty and students in Mumbai: a cross-sectional web-based e-survey study - Kamdin, Farzan; Khemani, Kruti; Varghese, Annamma (International Journal Of Community Medicine And Public Health, 2021)
Background: Coronavirus (COVID-19) has spread rapidly throughout the world leading to an emergency global pandemic. Among the varied affected sections of the population and healthcare, physiotherapy is no exception. To what extent, both the physical activity and anxiety levels have been affected amongst the physiotherapy practitioners, teaching faculty and students is not completely known. Hence, this study was undertaken. Methods: Among a potential 400 participants, 357 responded (response rate=89.25%). Cross-sectional web based open e-survey was sent using google forms via emails and social media platforms such as Whatsapp, facebook, instagram and linkedin messenger. The primary outcome measures were international physical activity questionnaire-short form (IPAQ-SF) for self-reported physical activity and general anxiety disorder (GAD-7) questionnaire for measuring self-reported anxiety. Results: Out of the 357 participants, 40 were inactive (<600 METs/week), 175 were minimally active (600-3000 METs/week) and 142 were health enhancing physically active (>3000 METs/week). The GAD-7 score showed a significant proportion of participants (74%) to have mild to moderate anxiety and only 26% had moderately severe to severe anxiety. Physiotherapy students were found to do least amount of physical activity in a week (mean METs/week of 2590) and were also more anxious with an average GAD-7 score of 7.7. Practicing physiotherapists and teachers had better scores of 3285 and 3028 METs/week and also better mean GAD-7 scores at 6.4 and 5.3, respectively. Conclusions: The lockdown caused by the COVID-19 pandemic has affected the physical activity levels and mental wellbeing of physiotherapy students more than the physiotherapy practitioners and teaching faculty.